The Impact of English as a Foreign Language Learning on Students' Algerian Lifestyle The Case of Master One Students at M’sila University - Ahmed ALLILI, Dr Noureddine REFICE (université mohamed boudiaf .m'sila, 2023)
Abstract Learning a new language can be the initial step towards embracing a new lifestyle. This study investigates the influence of EFL learning on students' Algerian lifestyle and identifies the main aspects that are affected by this process. It also aims to discover the main reasons and factors behind this influence. This study employs a mixed method approach. A questionnaire and an interview are used as the main data collection tools. The questionnaire has been administered to master one student from the two specialties in the English Department at the University of M'sila. The interview has been dedicated to the teachers of English to obtain more accurate results. The findings of this study reveal that master one students' lifestyle is really influenced by EFL learning at different levels and aspects such as behaviors, interests, attitudes, language use, body language and dressing style. This influence occurs due to the wrong practices of the learning process, reading, listening, watching, globalization, prestige, seeking superiority, adopting Western lifestyles and imitating native speakers. Ultimately, these findings would make a valuable academic contribution by enhancing the comprehension of the prevailing phenomenon. Finally, this study recommends conducting a detailed study about the role of teaching styles in changing students' lifestyle to address the current phenomenon from various angles.
Keywords: Keywords: EFL Learning, Students’ Algerian Lifestyle